The Language of Mass Architectural Postmodernity - Dimitrij Zadorin (Місто: історія, культура, суспільство, 2022)
Setting itself off against the architecture of the capitalist West, allegedly tangled in styles, Soviet architecture claimed its origins in the social realm. If one is to trace the intrinsic nature of changes in the architecture of the 1980s in the USSR, it is to be done not through the borrowed concept of postmodernism, but through the analysis of the developments in the design of its most social manifestation—mass housing. So far, Soviet architecture has primarily been whittled down to the evolution of styles. A more advanced reading focuses on the shift from Socialist Realism to the complex design of the human habitat following Khrushchev’s reforms in construction. However, even this transformation took place within the framework of building systematization, represented by the all-Union system of naming for standard architecture, or the Nomenclature. The system, implemented since 1947, assigned indexes to type designs of all building types; within it, every type design was allocated its specific position. The Nomenclature could thus describe the whole human habitat. In the mid-1980s, the naming system made further steps to meet the growing diversification of type designs by assigning new indexes which were longer and codified more parameters, undermining vested geographical and temporal hierarchies. The diversity was treated as a quantitative problem, which the Nomenclature successfully solved. It proved flexible enough to consistently ascribe an index to any—not necessarily type—design. Although mass housing disappeared from the architectural discourse during perestroika, standardized architecture enjoyed the most fruitful and systematic time in its history. So all-encompassing and everlasting, the Nomenclature nevertheless collapsed with the fall of the Soviet Union. The centralization of design proved its most fundamental precondition, which in the post-Soviet world was impossible to retain.